Penerapan Metode Heutogogi Dan Kirkpatrick Dalam Pelatihan Advanced Microsoft Excel Untuk Peningkatan Kompetensi Karyawan YPAC Jakarta - Anita Diana; Reva Ragam Santika (Universitas Mathla'ul Anwar Banten, 2022)
IMPLEMENTATION OF HEUTAGOGI AND KIRKPATRICK METHODS IN ADVANCED MICROSOFT EXCEL TRAINING TO INCREASE JAKARTA'S YPAC EMPLOYEES COMPETENCE. This community service activity aims to increase the competence of YPAC Jakarta employees by implementing the heutugogi and Kirikpatrick methods to measure success after training. This activity uses a qualitative approach and a quantitative approach to measure evaluation after training. The results of this activity reveal that the heutagogy method in training for employees can be implemented. first, the preparation of a learning contract agreed with the participants, second, the implementation of training oriented to the needs of data processing and case studies to partners, third, providing feedback by providing a forum for informal discussion and fourth, reflection for both tutors and trainees. The results of the evaluation based on the Kirkpatrick method identified that in stage 1 the reaction of the participants to the resource person was good, stage 2 in terms of attitudes, knowledge and skills were in the good category, stage 3 in terms of work behavior showed a significant increase and in stage 4 there was an increase in the performance of the participants after attended training. Training participants are able to improve their performance and can share their knowledge with their colleagues.